Research trends in cardiovascular tissue engineering from 1992 to 2022: a bibliometric analysis - Lai, Ping; Sheng, Ming; Ye, Jin-hua; Tang, Zhi-xian; Hu, Shuo; Wang, Bei; Yuan, Jing-lin; Yang, Yi-hong; Zhong, Yi-ming; Liao, Yong-ling (Frontiers in Cardiovascular Medicine, 2023)
Background: Cardiovascular tissue engineering (CTE) is a promising technique to treat incurable cardiovascular diseases, like myocardial infarction, ischemic cardiomyopathy. Plenty of studies related to CTE have been published in the last thirty years. However, an analysis of the research status, trends, and potential directions in this field is still lacking. The current study aims to reveal research trends, and potential directions on CTE by applying bibliometric analysis. Methods: On August 05, 2022, research articles and review papers on CTE were searched from the web of science core collections with inclusion and exclusion criteria. Publication trends, research directions, and visual maps in this field were obtained using Excel (Microsoft 2009), VOSviewer, and Citespace software.Results: From 1992 to 2022, a total of 2,273 documents were included in the final analysis. Publications on CTE shows an upward trend, from 1992 (number of publications (Np):1) to 2021 (Np:165). The United State (Np: 916, number of citations: 152,377, H-index: 124) contributes the most publications and citations in this field. Research on CTE has a wide distribution of disciplines are led by engineering (Np: 788, number of citations: 40,563, H-index: 105). "Functional maturation" (red cluster, average published year (APY): 2018.63, 30 times), "cell-derived cardiomyocytes" (red cluster, APY: 2018.43, 46 times), "composite scaffolds" (green cluster, APY: 2018.54, 41 times), maturation (red cluster, APY: 2018.17, 84 times) are the main emerging keywords in this area. Conclusion: Research on CTE is a hot research topic. The United States is a dominant player in CTE research. Interdisciplinary collaboration has played a critical role in the progress of CTE. Study on functional maturation and development of novel biologically relevant materials and related applications will be the potential research directions in 3 this field.